Turismo e a Comunidade Porto do Capim: uma análise da participação local nas políticas públicas no Centro Históricos de João Pessoa-PB - Silva, Silvonetto Oliveira da (2011)
The goal of this study was to analyse the Porto do Capim community‟s participation during the public policy making process for the Historical Center of João Pessoa in order to revitalize its monuments and urban structures so that the cultural tourism might be developed. Therefore, we approached a qualitative research, through semi-structured interviews, applied to the representatives of the Porto do Capim community, the State Government of Paraiba and the Municipality of João Pessoa managers, and representatives from the local tourist trade interested in the area. The data was analyzed by the technique of Content Analysis, which the main category of analysis was the participation. Thus, we conclude that the community participation is fragile on the public policy making process, whereas the sporadic meetings held by the government to discuss its actions with the community not involved in a deliberative democratic process so that the community members could interpose their needs and points of views.